Identification of critical enzymes in the salmon louse chitin synthesis pathway as revealed by RNA interference-mediated abrogation of infectivity. Issue 10 (September 2020) - Braden, Laura; Michaud, Dylan; Igboeli, Okechukwu O.; Dondrup, Michael; Hamre, Lars; Dalvin, Sussie; Purcell, Sara L.; Kongshaug, Heidi; Eichner, Christiane; Nilsen, Frank; Fast, Mark D.
Graphical abstract: Highlights: Knockdown of GFAT, CHS1 or CDA result in complete abrogation of infectivity in Lepeophtheirus salmonis. Compensatory mechanisms in the chitin synthesis pathway of L. salmonis rescue function after knockdown of AGM and UAP. Two putative CDA2s and one CDA5 have been identified in L. salmonis. Abstract: Treatment of infestation by the ectoparasite Lepeophtheirus salmonis relies on a small number of chemotherapeutant treatments that currently meet with limited success. Drugs targeting chitin synthesis have been largely successful against terrestrial parasites where the pathway is well characterised. However, a comparable approach against salmon lice has been, until recently, less successful, likely due to a poor understanding of the chitin synthesis pathway. Post-transcriptional silencing of genes by RNA interference (RNAi) is a powerful method for evaluation of protein function in non-model organisms and has been successfully applied to the salmon louse. In the present study, putative genes coding for enzymes involved in L. salmonis chitin synthesis were characterised after knockdown by RNAi. Nauplii I stage L. salmonis were exposed to double-stranded (ds) RNA specific for several putative non-redundant points in the pathway: glutamine: fructose-6-phosphate aminotransferase ( LsGFAT ), UDP-N-acetylglucosamine pyrophosphorylase ( LsUAP ), N-acetylglucosamine phosphate mutase ( LsAGM ), chitin synthase 1 ( LsCHS1 ), and chitin synthase 2 ( LsCHS2 ). Additionally, we targeted three putative chitin deacetylases ( LsCDA4557, 5169 and 5956 ) by knockdown. Successful knockdown was determined after moulting to the copepodite stage by real-time quantitative PCR (RT-qPCR), while infectivity potential (the number of attached chalimus II compared with the initial number of larvae in the system) was measured after exposure to Atlantic salmon and subsequent development on their host. Compared with controls, infectivity potential was not compromised in dsAGM, dsCHS2, dsCDA4557, or dsCDA5169 groups. In contrast, there was a significant effect in the dsUAP-treated group. However, of most interest was the treatment with dsGFAT, dsCHS1, dsCHS1+2, and dsCDA5956, which resulted in complete abrogation of infectivity, despite apparent compensatory mechanisms in the chitin synthesis pathway as detected by qPCR. There appeared to be a common phenotypic effect in these groups, characterised by significant aberrations in appendage morphology and an inability to swim. Ultrastructurally, dsGFAT showed a significantly distorted procuticle without distinct exo/endocuticle and intermittent electron dense (i.e. chitin) inclusions, and together with dsUAP and dsCHS1, indicated delayed entry to the pre-moult phase.